THE WORK-LIFE BALANCE OF BLUE-COLLAR WORKERS: THE ROLE OF EMPLOYEE ENGAGEMENT AND BURNOUT - Wardani, Laila Meiliyandrie Indah; Firmansyah, Rahmat (Konsorsium Psikologi Ilmiah Nusantara (KPIN))
Abstract — The purpose of this study was to determine the effect of employee engagement and burnout on the perception of work-life balance, particularly on blue-collar workers. The study sample comprised of 91 employees of the production section (blue-collar workers) in a multinational company in Jababeka-Cikarang. Sampling was carried out using a stratified technique of proportional approach. The instruments used in this study are The Utrecht Work Engagement Scale (UWES), Maslach Burnout Inventory (MBI-GS), and Work-Life Balance Scale. The study used primary data collection through survey method and secondary data from the company for analysis. Multiple regression analysis showed that employee engagement and burnout influence participants’ perceptions on work-life balance. The result indicates that employee engagement and burnout explained 17.6 percent on the variability of participants’ perceived work-life balance.Abstrak — Tujuan penelitian ini adalah mengetahui pengaruh employee engagement dan burnout terhadap work-life balance, terutama pada pekerja blue-collar. Sampel penelitian berjumlah 91 orang karyawan yang bekerja di bagian produksi (blue-collar workers) sebuah perusahaan multinasional di Jababeka-Cikarang. Pengambilan sampel dilakukan dengan menggunakan teknik stratified sampling dan pendekatan proposional. Instrumen yang digunakan untuk pengukuran employee engagement adalah Utrecht Work Engagement Scale (UWES), Maslach Burnout Inventory (MBI-GS), dan Work-Life Balance Scale. Data yang akan digunakan untuk analisis merupakan data primer yang diperoleh melalui metode survei dan data sekunder dari perusahaan. Hasil analisa regresi berganda menunjukkan adanya pengaruh yang positif antara employee engagement dan burnout terhadap work-life balance. Employee engagement dan burnout berkontribusi sebesar 17.6 persen terhadap varians skor persepsi work-life balance partisipan.